Changes in Timing, Duration, and Symmetry of Molt of Hawaiian Forest Birds - Freed, Leonard A.; Cann, Rebecca L. (PLOS ONE, 2012)
Food limitation greatly affects bird breeding performance, but the effect of nutritive stress on molt has barely been investigated outside of laboratory settings. Here we show changes in molting patterns for an entire native Hawaiian bird community at 1650–1900 m elevation on the Island of Hawaii between 1989–1999 and 2000–2006, associated with severe food limitation throughout the year beginning in 2000. Young birds and adults of all species took longer to complete their molt, including months never or rarely used during the 1989–1999 decade. These included the cold winter months and even the early months of the following breeding season. In addition, more adults of most species initiated their molt one to two months earlier, during the breeding season. Suspended molt, indicated by birds temporarily not molting primary flight feathers during the months of peak primary molt, increased in prevalence. Food limitation reached the point where individuals of all species had asymmetric molt, with different primary flight feathers molted on each wing. These multiple changes in molt, unprecedented in birds, had survival consequences. Adult birds captured during January to March, 2000–2004, had lower survival in four of five species with little effect of extended molt. Extended molt may be adaptive for a nutrient stressed bird to survive warm temperatures but not cool winter temperatures that may obliterate the energy savings. The changing molt of Hawaiian birds has many implications for conservation and for understanding life history aspects of molt of tropical birds.